BUMN DI BURSA EFEK INDONESIA - Ponariyati Ponariyati (STMIK Pringsewu, 2019)
This research was conducted to determine how much influence the influence of Debt, Capital and Profit on State-Owned Commercial Banks (Persero) both simultaneously partially (individually) or simultaneously (together) on Profits in State-Owned Commercial Banks (Persero) in Indonesia stock exchange. The financial phenomenon in state-owned banks generally looks good. The highest NPL (non-performing loans) value of 4.0% occurred in Bank Mandiri in 2016. This figure is close to insecure because Bank Indonesia has determined that the ratio of non-performing loans (NPL) is 5%. Meanwhile the highest value of banking capability in generating profits was at Bank Rakyat Indonesia with a value of 4.19% in 2015. This means that the greater the profit value, the better the ability of banks to generate profits.The population of this study is the authors take secondary data in the form of documents in the form of annual financial statements consisting of debt and capital and profits of state-owned banks on the Indonesia Stock Exchange in the period 2008-2017, where the data can be accessed directly at www.idx.co.id . The results of data processing using SPSS version 24 show that there is an influence (partially) between the Influence of Debt (X1) on the profit of BUMN banks in the Indonesia Stock Exchange (Y) of 16.4%, and there is an effect (partially) between the variables of Capital Effect (X2) on the profits of BUMN banks in the Exchange Indonesian Securities (Y) of 0.6% and the variable Debt Influence and Capital Influence together (simultaneously) affect the profit of BUMN banks in the Indonesia Stock Exchange by 16.6% while the rest are influenced by other factors not included in research model.